Heart Damage and Arrhythmias in Children After Coronavirus Infection: Early and Remote Observations - Shadieva Khalima Nuridinovna; Bazarova Nigina Sobirzhonovna; Abdukadirova Nargiza Batirbekovna (Genius Journals, 2023)
The article presents data on complications of coronavirus infection in children, such as carditis, cardiopathy and pericarditis, as well as rhythm and conduction disorders. Signs of carditis were detected in 7 (13.5%) children, signs of infectious-toxic cardiopathy in 15 (28.8%) children, exudative pericarditis – in 9 (17.3%) patients, and in 4 of them simultaneously with the detection of fluid and in the pleural cavity.Sinus tachycardia was observed in 76.9% of 52 patients, sinus bradycardia – in 3.8%, atrioventricular block 1 degree – in 3.8%, atrioventricular block 2 degree – in 3.8%, atrioventricular block 3 degree – in 1.9% of the child. Ventricular extrasystole was detected in 5.8%, and in 1 of them – by the type of bigemenia, in 1.9% – supraventricular tachycardia, in 3.8% – atrial rhythm, in 3.8% – pacemaker migration, in 23.1% of patients a significant (P
Keywords: coronavirus infection; children; carditis; cardiopathy